Pregnancy outcome and cost‐effectiveness comparisons of artificial cycle‐prepared frozen embryo transfer with or without GnRH agonist pretreatment for polycystic ovary syndrome: a randomised controlled trial. (6th September 2020) - Luo, L; Chen, M; Wen, Y; Zhang, L; Zhou, C; Wang, Q
Abstract : Objective: To compare the live birth rate and cost effectiveness of artificial cycle‐prepared frozen embryo transfer (AC‐FET) with or without GnRH agonist (GnRH‐a) pretreatment for women with polycystic ovary syndrome (PCOS). Design: Open‐label, randomised, controlled trial. Setting: Reproductive centre of a university‐affiliated hospital. Sample: A total of 343 women with PCOS, aged 24–40 years, scheduled for AC‐FET and receiving no more than two blastocysts. Methods: The pretreatment group ( n  = 172) received GnRH‐a pretreatment and the control group ( n  = 171) did not. Analysis followed the intention‐to‐treat (ITT) principle. Main outcome measures: The primary outcome measure was live birth rate. Secondary outcome measures included clinical pregnancy rate, implantation rate, early pregnancy loss rate and direct treatment costs per FET cycle. Results: Among the 343 women randomised, 330 (96.2%) underwent embryo transfer and 328 (95.6%) completed the protocols. Live birth rate according to ITT did not differ between the pretreatment and control groups [85/172 (49.4%) versus 92/171 (53.8%), absolute rate difference −4.4%, 95% CI −10.8% to 2.0% ( P  = 0.45). Implantation rate, clinical pregnancy rate and early pregnancy loss rate also did not differ between groups, but median direct cost per FET cycle was significantly higher in the pretreatment group (7799.2 versus 4438.9 RMB, OR = 1.9, 95%CI 1.2–3.4, P  < 0.001). Median direct cost per live birth was also significantly higher in the pretreatment group (15663.1 versus 8189.9 RMB, odds ratio [OR] = 1.9, 95% CI 1.2–3.8, P  < 0.001). Conclusions: Pretreatment with GnRH‐a does not improve pregnancy outcomes for women with PCOS receiving AC‐FET, but significantly increases patient cost. Tweetable abstract: For women with PCOS, artificial cycle‐prepared FET with GnRH agonist pretreatment provides no pregnancy outcome benefit but incurs higher cost. Tweetable abstract: For women with PCOS, artificial cycle‐prepared FET with GnRH agonist pretreatment provides no pregnancy outcome benefit but incurs higher cost.